IMPLEMENTATION OF ING MADYA MANGUN KARSA IN SMES IN YOGYAKARTA, INDONESIA AND COMMUNITY LEARNING CENTER IN SABAH, MALAYSIA - Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna; Nisa, Ana Fitrotun; Wahidah, Umi; Lada, Suddin Bin (International Journal of Engagement and Empowerment (IJE2), 2024)
This community service aims to explain the application of ing madya mangun karsa from Ki Hajar Dewantara's leadership trilogy to SMEs in Yogyakarta consisting of UMKM Pottery & Ceramic Crafts "Dwiyanto Ceramic," UMKM Azka Furniture Bantul, Rama Putra Motor Bantul, and schools in Malaysia namely the Community Learning Center (CLC). This abdimas method uses direct and indirect observation with interview techniques through the Zoom application. The concept used is that of ing madya man gun karst in overcoming ongoing problems and providing solutions to leaders and followers in achieving their vision and goals. Training seminars and workshops were held both offline and online. The results of the activities are the understanding and implementation of the ing madya mangun karsa leadership attitude in the Pottery & Ceramic Craft UMKM "Dwiyanto Ceramic," UMKM Azka Furniture Bantul, Rama Putra Motor Bantul, and the Community Learning Center (CLC).